2012
DOI: 10.4236/ce.2012.31009
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in Greek Music Curricula and Pedagogy: An Investigation of Greek Music Teachers’ Perceptions

Abstract: Creativity's enhancement through education has been widely discussed and promoted in Greece, especially in the past few decades. In the music domain, teaching philosophy and practice seem to focus on ways that can encourage children to learn and apply their knowledge through creative music activities. This paper reports on the outcomes of a study undertaken with 112 general music teachers of different ages and scientific backgrounds, who teach in 235 primary and secondary schools in Greece. Being the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
(34 reference statements)
1
12
0
Order By: Relevance
“…Only a handful of studies have examined directly pre-service (Crow, 2008;Kokotsaki, 2011Kokotsaki, , 2012 and in-service music teachers' conceptualizations of creativity (Odena, Plummeridge, & Welch, 2005;Zbainos & Anastasopoulou, 2012). In particular, Kokotsaki (2012) found that pre-service primary teachers who had more limited conceptions were inclined to view creativity as dependent on the ability of the child rather than on the teacher's skill and expertise to foster creativity in the classroom.…”
Section: Music Teachers' Thinking About Creativitymentioning
confidence: 99%
See 2 more Smart Citations
“…Only a handful of studies have examined directly pre-service (Crow, 2008;Kokotsaki, 2011Kokotsaki, , 2012 and in-service music teachers' conceptualizations of creativity (Odena, Plummeridge, & Welch, 2005;Zbainos & Anastasopoulou, 2012). In particular, Kokotsaki (2012) found that pre-service primary teachers who had more limited conceptions were inclined to view creativity as dependent on the ability of the child rather than on the teacher's skill and expertise to foster creativity in the classroom.…”
Section: Music Teachers' Thinking About Creativitymentioning
confidence: 99%
“…Last but not least, in a study of how Greek in-service music teachers conceptualize creativity (Zbainos & Anastasopoulou, 2012), creativity was believed to be an innate characteristic that could not be promoted in all students. Participants had difficulty in identifying creative and non-creative situations and further, omitted composition when asked to report incidents of creativity in their teaching practice.…”
Section: Music Teachers' Thinking About Creativitymentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual reality solves the problem that perception and action separating, leads the perception and action study more natural, improves the study ecological validity, and holds great promise for the study of perception-action. In decades, researches about the relationship between perception and action in baseball, handball and tennis found that, athletes can make exact interceptive actions in virtual environment [11]. Figure 1 shows an instrument playing system based on the visual reality technology.…”
Section: IImentioning
confidence: 99%
“…Ministry of education on the education facing the 21sl century revitalization action plan [5], the article has made clear that are widely used in the modern information technology in education leads to profound changes in the education system. In terms of vocal music education field, the category of longitudinal fine development and integration with other subjects is an important trend of the development of the contemporary vocal music, increasing its total knowledge information geometric type [6][7]. Reflected in the vocal music discipline, mainly to enrich the song theory, a new mechanism and singing techniques and style of the deepening of the study, with the integration of related subjects and infiltration is increasingly strengthened [8].…”
mentioning
confidence: 99%